Mathepoly: exploring the impact of gamification on students’ motivation and engagement in mathematics - Tengku Samsudin, Tengku Alias (Asian Scholars Network, 2025)
The declining interest of Malaysian students in Science, Technology, Engineering and Mathematics (STEM) education is alarming in preparing them for Industry Revolution 4.0. Despite efforts to enhance STEM education, students STE Mathematics subjects to be dry and unengaging, largely due to traditional teaching methods that fail to inspire curiosity and enthusiasm. For this reason, it has become necessary to develop educational strategies utilizing gamification and technology to maintain student interest. Gamification that involves adding game-like elements to classroom settings has become increasingly popular in education, especially for teaching Mathematics. Researchers have studied how gamification can boost student engagement, motivation, and learning experience. This study is to explore the impact of gamification in Mathematics education through the creation and implementation of "Mathepoly", a game inspired by the classic Monopoly but infused with mathematical concepts and technology. Incorporating Mathepoly board with QR codes linked to Quizizz platform enhances the application of technology and makes the learning experience more engaging. This study employed quantitative analysis based on questionnaire adapted from ARCS model incorporate three components of motivation; attention (A), confidence (C), and satisfaction (S). One of the ARCS components which is relevant (R) was replaced with perceived learning effects (PLE). Two components corresponding to engagement, both emotional and cognitive also included. The questionnaire includes 20 items that used a 5-point Likert scale. The results indicated that gamification through Mathepoly increase student motivation and engagement. Additionally, there are significant positive correlation between motivation and engagement. Thus, this indicates a high impact of using Mathepoly as a gaming tool for mathematics education.